Answer:
f( x ) = - x² - x + 42
Explanation:
The polynomial function will have to include the zeroes with opposing signs, considering that when you isolate the value x say, you will take that value to the opposite side, changing the signs,
f(x) = (x + 7)(x - 6)
Now as you can see, x extends to negative infinity, such that,
f(x) = - (x + 7)(x - 6) - that negative makes no difference whatsoever on the zeroes of the function. All we want to do now is to expand this, and we receive out simplified solution.
Goal :
,
=
=
,
Expanded Solution :
,
Polynomial Function : f( x ) =